Homozygosity for the SCN10A Polymorphism rs6795970 Is Associated With Hypoalgesic Inflammatory Bowel Disease Phenotype - Gonzalez-Lopez, Eugene; Imamura Kawasawa, Yuka; Walter, Vonn; Zhang, Lijun; Koltun, Walter A.; Huang, Xuemei; Vrana, Kent E.; Coates, Matthew D. (Frontiers in Medicine, 2018)
Background: Hypoalgesic inflammatory bowel disease (IBD), a condition in which patients with active disease do not perceive and/or report abdominal pain, is associated with serious complications and there is a lack of cost-effective, reliable diagnostic methods to identify “at-risk” patients. The voltage-gated sodium channels (VGSC’s), Nav1.7, Nav1.8 and Nav1.9, are preferentially expressed on nociceptive neurons, and have been implicated in visceral inflammatory pain. At least 29 VGSC single nucleotide polymorphisms (SNPs) have been implicated in chronic somatic pain syndromes, but little is known about their role in human visceral sensation. We hypothesized that disruptive VGSC polymorphisms result in anti-nociceptive behavior in IBD. Methods and Findings: We performed targeted exome sequencing and/or TaqMan genotyping to evaluate the Nav1.7, Nav1.8 and Nav1.9 genes (SCN9A, SCN10A and SCN11A) in 121 IBD patients (including 41 “hypoalgesic” IBD patients) and 86 healthy controls. Allelic and genotypic frequencies of polymorphisms were compared among study groups who had undergone characterization of intestinal inflammatory status and abdominal pain experience. Forty-nine total exonic SNPs were identified. The allelic frequency of only one non-synonymous SNP (rs6795970 [SCN10A]) approached significance in hypoalgesic IBD patients when compared to other IBD patients (p=0.096, Fisher’s exact test). Hypoalgesic IBD patients were more likely to be homozygous for this polymorphism (46% vs. 22%, p=0.01, Fisher’s exact test). Conclusions: This is the first human study to demonstrate a link between a genetic variant of SCN10A and abdominal pain perception in IBD. These findings provide key insights into visceral nociceptive physiology and new diagnostic and therapeutic targets to consider in IBD and other gastrointestinal conditions associated with chronic abdominal pain. Further studies are required to elucidate the precise pathophysiological impact of the rs6795970 polymorphism on human gastrointestinal nociception.